2007
DOI: 10.4319/lo.2007.52.3.1239
|View full text |Cite
|
Sign up to set email alerts
|

Wood biofilm as a food resource for stream detritivores

Abstract: Published assimilation efficiencies indicate that leaf detritus is a more nutritious food for stream invertebrates than wood. Some studies, however, suggest that wood and wood biofilms (epixylon) may be an important but overlooked resource. We measured assimilation efficiencies of three detritivores for leaves and epixylon and compared attributes of grazed versus ungrazed wood epixylon to assess its use by detritivores. Pycnopsyche gentilis (Trichoptera), Tipula abdominalis (Diptera), and Tallaperla spp. (Plec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 37 publications
3
53
0
Order By: Relevance
“…is 4 to 253 larger than the other species used and shredder biomass was balanced explicitly among treatments. However, limnephilid caddisflies are often the functionally dominant detritivores in streams (Herbst 1980, 1982, Eggert and Wallace 2007, Creed et al 2009). Creed et al (2009) found that Pycnopsyche gentilis was both a competitive dominant and a very effective shredder.…”
Section: Discussionmentioning
confidence: 99%
“…is 4 to 253 larger than the other species used and shredder biomass was balanced explicitly among treatments. However, limnephilid caddisflies are often the functionally dominant detritivores in streams (Herbst 1980, 1982, Eggert and Wallace 2007, Creed et al 2009). Creed et al (2009) found that Pycnopsyche gentilis was both a competitive dominant and a very effective shredder.…”
Section: Discussionmentioning
confidence: 99%
“…Wood pieces provide stable substrate for invertebrates and biofilms, entrap leaves and other organic matter, afford overhead cover for fish, promote hyporheic exchange flow and transient storage, enhance hydraulic heterogeneity, and encourage pool formation and channel meandering [Angermeier and Karr, 1984;Beechie and Sibley, 1997;Gregory et al, 2003;Johnson et al, 2003;Mutz and Rohde, 2003;Eggert and Wallace, 2007;Stofleth et al, 2008]. The frequency and character of wood inputs varies in space and time [Latterell and Naiman, 2007;Golladay et al, 2007] and is strongly affected by riparian management [Flebbe and Dolloff, 1995;Angradi et al, 2004;Kreutzweiser et al, 2005;Czarnomski et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Epixylic biofilm development on incubated alder branches Driving factors of periphyton biofilm dynamics in streams reported so far were light availability and water temperature (Kiffney et al, 2003), dissolved nutrient concentrations (Tank and Dodds, 2003), grazing by invertebrates (Eggert and Wallace, 2007) and moving sediments that abrades periphyton during peak flow events (Biggs et al, 1999). Epixylic biofilms in both study streams reached maximum concentrations of chl a in May when temperature became warmer and sun light reached the stream bottom as canopy was not fully closed, yet.…”
Section: Discussionmentioning
confidence: 99%
“…Submerged wood in streams, represented mainly by medium sized branches with lengths <100 cm and diameters <10 cm (Elosegi et al, 1999), serves as habitat (Hoffmann and Hering, 2000;Benke and Wallace, 2003) and food (Pereira et al, 1982) for many invertebrate species. It provides a carbon source for wood-degrading bacteria and fungi (Gulis et al, 2008) and, finally, provides an attachment site for epixylic biofilm Sabater et al, 1998;Spa¨nhoff et al, 2006) that serves as additional food source for invertebrates (Eggert and Wallace, 2007).…”
Section: Introductionmentioning
confidence: 99%